Time-dependent Photoionization Modeling of Warm Absorbers in Active Galactic Nuclei - Sadaula, Dev R.; Bautista, Manuel A.; García, Javier A.; Kallman, Timothy R. (Astrophysical Journal, 2023)
Warm absorber spectra contain bound-bound and bound-free absorption features seen in the X-ray and UV spectra from many active galactic nuclei. The widths and centroid energies of these features indicate they occur in outflowing gas, and the outflow can affect the gas within the host galaxy. Thus, the warm absorber mass and energy budgets are of great interest. Estimates for these properties depend on models that connect the observed strengths of the absorption features with the density, composition, and ionization state of the absorbing gas. Such models assume that the ionization and heating of the gas come primarily from the strong continuum near the central black hole. They also assume that the various heating, cooling, ionization, and recombination processes are in a time-steady balance. This assumption may not be valid, owing to the intrinsic time variability of the illuminating continuum or other factors that change the cloud environment. This paper presents models for warm absorbers that follow the time dependence of the ionization, temperature, and radiation field in warm absorber gas clouds in response to a changing continuum illumination. We show that the effects of time variability are important over a range of parameter values, that time-dependent models differ from equilibrium models in meaningful ways, and that these effects should be included in models that derive properties of warm absorber outflows.
CRIS-Team Scopus Importer:2023-04-21